Divine justice - Baldacci, David , 1960- (Grand Central, 2009)
Known by his alias, "Oliver Stone," John Carr is the most wanted man in America. With two pulls of the trigger, the men who destroyed Stone's life and kept him in the shadows were finally silenced. But his freedom comes at a steep price: The assassinations he carried out prompt the highest levels of the U. S. government to unleash a massive manhunt. Yet behind the scenes, master spy Macklin Hayes is playing a very personal game of cat and mouse